> 数学 >
(3x-2)(2x-3)=(6x=5)(x-1)+15解方程
计算:(1)-10xy*(2x的平方-3xy的平方)
(2)(-2x的平方)*(-y)+3xy*(1-三分之一x)
(3)3a(2a的平方-9a+3)-4a(2a-1)
(4)(-2x的平方)的平方*(-3x)的立方
先化简在求值 x(x-1)+2x(x+1)-(3x-1)(2x-5) 其中x=2
快快 快的加财富值
人气:259 ℃ 时间:2019-12-13 14:25:13
解答
(3x-2)(2x-3)=(6x-5)(x-1)+15
——》6x^2-13x+6=6x^2-11x+5+15
——》x=-7;
1、原式=-10xy*(2x^2-3xy^2)=30x^2y^3-20x^3y;
2、原式=2x^2y+3xy-x^2y=x^2y+3xy;
3、原式=6a^3-27a^2+9a-8a^2+4a=6a^3-35a^2+13a;
4、原式=4x^4*(-27x^3)=-108x^7;
5、原式=x^2-x+2x^2+2x-6x^2+17x-5
=-3x^2+18x-5
=-3*4+18*2-5
=19.
推荐
猜你喜欢
© 2024 79432.Com All Rights Reserved.
电脑版|手机版